Analisis Pelaksanaan Rekrutmen Pada Villa Song Broek Di Kecamatan Payangan Kabupaten Gianyar - Indriani, Kadek Cindy; Sujana, I Nyoman (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the employee recruitment process at Villa Song Broek, the obstacles faced in the process of recruiting employees at Villa Song Broek, and the solutions to overcome the obstacles that occur in recruitment at Villa Song Broek. This type of research is descriptive research. The subjects of this study were the villa owners, managers, and employees at the villa. The object of this research is the implementation of recruitment at Villa Song Broek. Collecting data using interviews. Furthermore, the data were analyzed using data triangulation techniques. The results showed that in the implementation of recruitment at Villa Song Broek, there were several stages of the recruitment process that were different from the theory of the supposed recruitment process. In the recruitment process at the villa, there are no stages such as determining the basis of recruitment, identifying vacant positions, seeking job information through job analysis, and selecting candidates.